Bystander influence of nematode exposure on subsequent herpesvirus infections in vivo - Chetty, Alisha (Department of Pathology, 2022)
Parasitic worms have the ability to modulate the hosts immune response to promote host control of the infection and also parasite survival in the host. Helminth infections classically induce a potent Th2-biased and regulatory immune imprint. This immune response also influences unrelated inflammatory processes in the host. Studies have shown helminth infections have bystander influences on unrelated conditions such as allergy and autoimmunity. Additionally, helminth infections can alter susceptibility to other infections. In this thesis, we investigate the systemic influences of murine nematode Nippostrongylus brasiliensis infection on host immunity in colonized and non-colonized tissues, and the implications of these effects on susceptibility to subsequent herpesvirus infections in vivo. We show that prior N. brasiliensis infection enhanced control of acute respiratory murid gammaherpesvirus (MuHV-4) infection, with an increase in viral-specific CD8+ T cells in colonized lung tissue. Enhanced effector cytokine responses by cytotoxic T cells were also observed with prior helminth exposure. Conversely, despite enhanced primary control, prior helminth exposure was associated with earlier and heightened genital reactivation of MuHV4. This demonstrates differences in local bystander and systemic effects of helminth exposure on the host, and on unrelated viral infections. We also show that N. brasiliensis infection, which transits the respiratory and gastrointestinal tracts, also systemically influences immunity in the female genital tract (FGT) in vivo. Here, helminth infection induced Th2-type immunity in the FGT, namely increased tissue IL-4, IL-5 and long-lasting eosinophilia. We further demonstrated that systemic influences of N. brasiliensis infection results in exacerbated genital pathology and inflammation, following subsequent intravaginal herpes simplex virus type II (HSV-2) infection. Increased HSV-2 pathology with prior helminth exposure was associated with diminished innate anti-viral immunity, increased IL-33, ILC2 and IL-5 responses, as well as significant eosinophilia. Interestingly, abolition of canonical Th2 immune signalling by the lack of IL-4Rα expression, enhanced innate anti-viral defences and provided protection from HSV-2 pathology. However, N. brasiliensis-induced exacerbation of HSV-2 illness was IL-4Rαindependent, associated with significant genital eosinophilia. Furthermore, antibody-depletion of eosinophils ameliorated nematode-exacerbated HSV-2 pathology, suggesting that nematode-induced genital eosinophilia mediates increased HSV-2 pathology in coinfected mice. We have therefore shown that helminth infections can induce local and systemic bystander immunity to lymphoid and myeloid immune compartments, which alters susceptibility to subsequent herpesvirus infections.